Innovation in Medicine and Healthcare 2016 - Chen, Yen-Wei; Tanaka, Satoshi; Howlett, Robert J.; Jain, Lakhmi C. (Smart Innovation, Systems and Technologies,, 2016)
This proceedings volume includes 32 papers, which present recent trends and innovations in medicine and healthcare including Innovative Technology in Mental Healthcare; Intelligent Decision Support Technologies and Systems in Healthcare; Biomedical Engineering, Trends, Research and Technologies; Advances in Data & Knowledge Management for Healthcare; Advanced ICT for Medical and Healthcare; Healthcare Support System; and Smart Medical and Healthcare System. Innovation in medicine and healthcare is an interdisciplinary research area, which combines the advanced technologies and problem solving skills with medical and biological science. A central theme of this proceedings is Smart Medical and Healthcare Systems (modern intelligent systems for medicine and healthcare), which can provide efficient and accurate solution to problems faced by healthcare and medical practitioners today by using advanced information communication techniques, computational intelligence, mathematics, robotics and other advanced technologies. .